2008
DOI: 10.1507/endocrj.k07e-138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of New-onset Diabetes on Arterial Stiffness after Renal Transplantation

Abstract: Abstract. New-onset diabetes after renal transplantation (NODAT) is known to be a potent risk factor for cardiovascular events. We therefore investigated the incidence and risk factors for NODAT, and evaluated surrogate endpoints of atherosclerosis in Japanese patients with stable renal function after renal transplantation. Seventy-nine patients were enrolled in the study, and a 75 g oral glucose tolerance test (OGTT) was performed in subjects excluding patients with known NODAT. We evaluated the risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A number of studies revealed that restoration of renal function after renal transplantation could partially improve increased arterial stiffness [ 20 , 21 ]. On the other hand, it has also been shown that renal transplant recipients with glucose intolerance had increased PWv, suggesting that glucose intolerance may induce atherosclerosis [ 4 , 5 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies revealed that restoration of renal function after renal transplantation could partially improve increased arterial stiffness [ 20 , 21 ]. On the other hand, it has also been shown that renal transplant recipients with glucose intolerance had increased PWv, suggesting that glucose intolerance may induce atherosclerosis [ 4 , 5 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma adiponectin levels in humans are significantly lower among subjects who are obese, display coronary artery disease caused by atherosclerosis, and have hypertension [6–8]. In NODAT patients, the degree of atherosclerosis determined by brachial‐ankle pulse wave velocity was shown to increase with a decrease in adiponectin level [9]. In addition, this secretory protein may be involved in the pathogenesis of type 2 diabetes mellitus, based on its relationship with insulin and glucose metabolism [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that a low pre-transplant serum adiponectin level is a predictor of arterial stiffness and NODAT in renal transplant patients, with a significant inverse correlation found between mean pre-transplant serum adiponectin and ba-PWV levels. Previous studies have demonstrated that a low serum adiponectin level is an independent predictor of high baPWV level in essential hypertension [9] and renal transplant [10] patients. Our results support those findings.…”
Section: Discussionmentioning
confidence: 96%